2019
DOI: 10.1093/infdis/jiz590
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Exposure but Not Early Cytomegalovirus Infection Is Associated With Increased Hospitalization and Decreased Memory T-Cell Responses to Tetanus Vaccine

Abstract: Background Human immunodeficiency virus (HIV)-exposed, uninfected (HEU) infants experience high rates of infectious morbidity. We hypothesized that early cytomegalovirus (CMV) infection was associated with increased hospitalization rates and decreased vaccine responses in HEU compared with HIV-unexposed (HUU) infants. Methods Among infants enrolled in the Tshipidi study in Botswana, we determined CMV infection status by 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…Although studies conducted before the wide adoption of perinatal ARV treatment reported heightened immune activation and/or exhaustion in iHEU 48 , 49 , more recent studies have shown reduced or impaired memory T cells among iHEU compared to iHUU 17 , 50 52 . Such T cell alterations were associated with poor responses to vaccines and/or increased hospitalisation 50 , 51 . Other viral infections occurring during pregnancy such as SARS-Cov2 have also been documented to alter infant immunity even in the absence of viral transmission 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Although studies conducted before the wide adoption of perinatal ARV treatment reported heightened immune activation and/or exhaustion in iHEU 48 , 49 , more recent studies have shown reduced or impaired memory T cells among iHEU compared to iHUU 17 , 50 52 . Such T cell alterations were associated with poor responses to vaccines and/or increased hospitalisation 50 , 51 . Other viral infections occurring during pregnancy such as SARS-Cov2 have also been documented to alter infant immunity even in the absence of viral transmission 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In infants with antenatal or postnatal CMV infection, studies have also evaluated the effect of CMV on response to vaccines, especially in poor-resource settings where the majority of children are infected before their first year of life [ 73 ]. CMV-induced alterations of immune response to measles and to a lesser extent to polio vaccines have been reported, whereas no difference in the response to Hib or tetanus vaccines were reported [ 74 , 75 ]. Interestingly, a study evaluating the immune response to oral polio vaccine in Zambian infants suggested a synergistic negative effect of HIV and CMV coinfection on the antibody response [ 76 ].…”
Section: Impact Of CMV Infection On Response To Pathogens and Vaccinesmentioning
confidence: 99%
“…Однак висновки дослідників відносно впливу герпесвірусної інфекції на імунну відповідь далеко не однозначні. На думку одних авторів, в інфікованих герпесвірусами осіб гальмується реакція імунної системи [6,7], натомість ряд інших дослідників схиляється до думки, що герпесвіруси навпаки мають імуномоделювальний ефект [4,8,9]. Суперечливість даних простежується в доступній літературі і стосовно реакції інтерлейкінів крові дітей, інфікованих і неінфікованих герпесвірусами [10,11].…”
Section: харківський національний медичний університетunclassified